MODEL KONSEPTUAL SANITASI PERMUKIMAN BERBASIS THAHARAH DI KOMUNITAS DAS - Pratiwi, Anggie; Safitriana Bey; Dhevi Mulyanda; Lily Endah Diansari; Nurul Aina Syahira (Nusantara Hasana Journal, 2025)
Residential areas along the Palembang River Basin (DAS) still face serious sanitation issues. Domestic waste dumped directly into the river, the habit of washing and bathing in the same water, and low awareness of cleanliness are recurring patterns. This study aims to develop a conceptual model of residential sanitation based on the value of thaharah from an Islamic environmental theology perspective. The study was conducted in RT 7, Keluruhan 15 Ulu, Jakabaring District, Palembang, using descriptive-quantitative methods. The research approach is a thematic-maudhu'i interpretation of the verses of the Qur'an through the word "Thaharah" which is then linked to an analysis of technical regulations (Minister of Health Regulation No. 2 of 2023, SNI 8153:2015, and Minister of Public Works and Housing Regulation No. 4 of 2017), as well as field observations. The results indicate a gap between the community's religious understanding and daily hygiene practices. The developed thaharah-sanitas model contains four pillars: personal and water hygiene, social hygiene, environmental hygiene, and clarity of intention. This concept has the potential to become a theological instrument to strengthen value-based sanitation policies and become a reference in sustainable environmental hygiene education.